Expanded distribution and a new genus for rock-inhabiting sea pens (Cnidaria, Anthozoa, Octocorallia, Pennatuloidea) - Ganguly, Upasana; France, Scott C. (Zootaxa, 2024)
Sea pens (Superfamily Pennatuloidea) are a specialized group of octocorals that evolved to live embedded in a soft-sedimented seafloor using their peduncles as anchors. Rock-inhabiting sea pens (“rock pens”) were first described in 2011; their peduncle is modified into a suction cup-like structure that allows them to attach onto the surface of hard substrates, an adaptation previously unknown in sea pens. There are currently four species that have been identified as rock pens based on their peduncular morphology: three of these are in the genus Anthoptilum (Anthoptilidae), and one in the genus Calibelemnon (Scleroptilidae). Herein, we explore the geographic distribution and depth ranges of rock pens using observations from remotely operated vehicles and investigate the evolutionary origins of the rock pens. We present a phylogenomic study of sea pens, based on DNA sequences from hundreds of ultraconserved elements (UCE) and compare these trees to those constructed using mitochondrial gene regions. Our results show that the ancestral sea pen had a typical elongated peduncle. The adaptation to attach onto hard, rocky substrates using the special suction cup-like peduncle evolved along a single derived lineage that is sister to a lineage comprising the genus Anthoptilum. We propose all known rock pen species be grouped into a single new genus, described herein, in the family Anthoptilidae, to reflect the phylogenetic history.